Etika Bisnis dalam Akuntansi Menurut Perspektif Surat Al-Baqarah Ayat 282 - Nimatul Fitria Mukaromah; Amin Wahyudi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Sharia accounting is no longer something new nowadays. In sharia accounting, there is a cleanup of assets as a responsibility in the form of a financial report on the use of funds. However, the facts in the field are that there are many cases in the field related to fraudulent transactions in accounting reports which can cause losses to many parties. For example, PT KAI, Jiwasraya, Garuda Indonesia, etc. Of course, this is not in line with Islamic business ethics which always pay attention to the benefit of all parties. In Surah al-Baqarah verse 282 also contains values ​​related to accounting principles, namely accountability, justice, truth and honesty. For this reason, in this research the researcher used a qualitative approach with a library study method and utilized information sources from the internet. With the aim of exploring and providing solutions regarding abuses of accountability when related to Islamic business ethics based on the perspective of al-Baqarah verse 282. The result is in Surah al-Baqarah verse 282 which includes the principles of accountability, justice and truth. Therefore, this verse can be implemented in business because it is important for companies to implement sharia accounting which is based on the values ​​contained in this verse, so that they can produce healthy and responsible financial reports in accordance with Islamic business ethics.